Multiple Odontogenic Keratocysts in a Non-syndromic Young Patient: An Unusual Case Report - Mishra, Ravish; Kandel, Laxmi; Yadav, Deepak; Tripathi, Shashank; Karki, Bijay; Chaurasia, Nitesh; Singh, Sunil Kumar (Journal of Universal College of Medical Sciences, 2021)
Odontogenic keratocyst (OKC) is a benign intraosseous lesion with invasive and aggressive behavior. It comprises approximately 2-21.8% of all jaw cysts. Odontogenic keratocysts (OKCs) are believed to arise from remnants of the dental lamina most common site in the molar ramus area. OKCs have a specific histopathologic appearance and are found to be locally aggressive and have a high recurrence rate, thus requires close long-term follow-up. OKCs are one component of the Gorlin-Goltz syndrome and all patients with multiple OKCs should be evaluated for this syndrome. In this paper, we present a case of a 13-year old non-syndromic female patient with multiple OKCs located at symphysis and bilateral mandibular angle region who was treated surgically with no obvious post-operative complications during follow-up period.